Incorporation of niacinamide, L-carnosine, hesperidin, and a Heat Shock Protein 70 homologue into collagen matrices : implications on dermal fibroblast activity and wound healing - Pretorius, Etheresia (University of Pretoria, 2013)
Thesis (PhD (Anatomy))--University of Pretoria, 2010.